2003
DOI: 10.1093/pasj/55.5.l61
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of Interacting Molecular Gas toward the TeV Gamma-Ray Peak of the SNR G 347.3–0.5

Abstract: Supernova remnants ($=$ SNR) are suggested to be sites of cosmic-ray acceleration. In particular, it has been an issue of keen interest whether cosmic ray protons are being accelerated in a SNR which emits TeV $\gamma$-rays. A crucial observational test for this is to find dense molecular gas towards the SNR, because such molecular gas can best verify the existence of cosmic-ray protons via pion decay to $\gamma$-rays. Here, we show that new high-resolution mm-wave observations of interstellar CO molecule have… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

12
158
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 157 publications
(170 citation statements)
references
References 12 publications
12
158
0
Order By: Relevance
“…The distance and age of RXJ1713.7−3946 are estimated to be 0.9-1.3kpc and ∼1600yr, respectively (Fukui et al 2003;Moriguchi et al 2005), which is consistent with its connection with the guest star AD393 (e.g., Wang et al 1997). This age estimate is supported by its fast shock velocity (Katsuda et al 2015) and the similarities of its other observed properties to other young SNRs.…”
Section: Origin Of Gamma Rays From Snr Rxj17137−3946supporting
confidence: 58%
See 1 more Smart Citation
“…The distance and age of RXJ1713.7−3946 are estimated to be 0.9-1.3kpc and ∼1600yr, respectively (Fukui et al 2003;Moriguchi et al 2005), which is consistent with its connection with the guest star AD393 (e.g., Wang et al 1997). This age estimate is supported by its fast shock velocity (Katsuda et al 2015) and the similarities of its other observed properties to other young SNRs.…”
Section: Origin Of Gamma Rays From Snr Rxj17137−3946supporting
confidence: 58%
“…Although weak thermal X-ray emission has recently been detected from the SNR interior (Katsuda et al 2015), the X-ray emission is still dominated by synchrotron radiation, which links directly to the existence of high-energy electrons. Radio observations of CO and H I gas have revealed a highly inhomogeneous medium surrounding the SNR, such as clumpy molecular clouds (Fukui et al 2003Fukui 2013;Moriguchi et al 2005;Sano et al 2010Sano et al , 2013Sano et al , 2015. Another radio observation of CS also confirmed the existence of a very dense (>10 5 cm −3 ) ISM core toward the SNR (Maxted et al 2012).…”
Section: Origin Of Gamma Rays From Snr Rxj17137−3946mentioning
confidence: 94%
“…The contribution of this component should be significantly enhanced when the supernova shell overtakes nearby dense molecular clouds 21 , as seems to be the case for this object. The CO data 22 suggest that a cloud is interacting with the northwestern part of the SNR, where a striking spatial coincidence between the CO density peaks and the regions of peak X-ray emission is seen. The X-ray data 23 also indicate significant absorption column densities in the western part of the remnant, at values about twice those to the east.…”
mentioning
confidence: 91%
“…Given the recent estimates [22][23][24] of the distance to the source of 1 kpc, if a significant part of the TeV flux were to be formed by interactions of cosmic-ray nuclei with gas atoms in the cloud with density n exceeding 100 cm −3 , the energetics implied by the γ-ray flux and the spectrum would be a few times 10 49 n −1 erg between 10 and 100 TeV. This is consistent with the picture of an SNR origin of Galactic cosmic rays involving about 10% efficiency for conversion of the mechanical energy of the explosion into non-thermal particles, and a production spectrum in the SNR which is approximately an E −2 power law from several GeV to about one PeV.…”
mentioning
confidence: 99%
“…The shock velocity is based on the likely distance of 1 kpc (Fukui et al, 2003), a possible age of 1600 yr (Wang et al, 1997) and an assumed m = 0.55; the density is an upper limit (Hiraga et al, 2005). 8 m is here assumed, but Vs is based on the expansion measurement of Katsuda et al (2008) and their assumed distance of 1 kpc.…”
mentioning
confidence: 99%